An environmental perspective on developing dual energy storage for electric vehicles—a case study exploring Al-ion vs. supercapacitors alongside Li-ion - Melzack, N.; Wills, R. G. A.; Cruden, A. J. (Frontiers in Energy Research, 2024)
Much focus of dual energy storage systems (DESS) for electric vehicles (EVs) has been on the cost reduction and performance enhancement. While these are important in the development of better systems, environmental impacts of system and component level choices should not be overlooked. Current interest in EVs is primarily motivated by environmental reasons such as climate change mitigation and reduction of fossil fuel use, so it is important to develop environmentally sound alternatives at the design stage. Assessing the environmental impact of developmental and mature chemistries provides valuable insights into which technologies to select now and which to develop for the future. This paper presents a cradle-to-gate (i.e., all raw material and production elements are considered however the 'use' phase and recycling are not) lifecycle assessment of a DESS with Liion and aqueous Al-ion cells, and one with Li-ion cells and supercapacitors. These are also compared to a full Li-ion EV battery in terms of their environmental impact for both a bus and car case study. Key findings show that the use of a DESS overall reduces the environmental impacts over the vehicle lifetime and provides an argument for the further development of aqueous Al-ion cells for this application.